2021
DOI: 10.3390/jcm10215006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Masticatory Performance of Maxillary Mini Dental Implant Overdentures, Complete Removable Dentures and Dentate Subjects

Abstract: Background: Mini dental implant (MDI) overdenture rehabilitation for the edentulous maxilla is a valuable, less invasive and affordable treatment alternative for complete removable dentures (CRD). However, comparative quantification of masticatory performance in different oral conditions are scarce. Purpose: This study compares objective masticatory performance of dentate groups, maxillary CRD and MDI overdentures and subjective masticatory performance in maxillary CRD and MDI overdentures. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…The research of Sharma et al [ 25 ] offered evidence that the replacement of mandibular conventional denture with an implant-supported mandibular overdenture considerably reduces mean particle size. Disagreeing with the previous study, but in accordance with this study’s results, the randomized controlled trial reported by Fontijn-Tekamp et al [ 26 ] found that there is no difference between patients with complete dentures and implant overdentures regarding food comminution, and the study of Van Doorne et al [ 8 ] showed that objective masticatory performance is similar in wearers of complete denture and mini dental implant overdentures. The lack of improvement of food fragmentation in mandibular implant overdentures compared to conventional dentures might be related to retention and stability problems, known as factors that impair mastication in bimaxillary complete denture wearers [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The research of Sharma et al [ 25 ] offered evidence that the replacement of mandibular conventional denture with an implant-supported mandibular overdenture considerably reduces mean particle size. Disagreeing with the previous study, but in accordance with this study’s results, the randomized controlled trial reported by Fontijn-Tekamp et al [ 26 ] found that there is no difference between patients with complete dentures and implant overdentures regarding food comminution, and the study of Van Doorne et al [ 8 ] showed that objective masticatory performance is similar in wearers of complete denture and mini dental implant overdentures. The lack of improvement of food fragmentation in mandibular implant overdentures compared to conventional dentures might be related to retention and stability problems, known as factors that impair mastication in bimaxillary complete denture wearers [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…State-of-the-art research into masticatory performance highlights the importance of both subjective and objective methods of evaluation, as it is able to produce complementary data, frequently showing a weak association [ 6 , 7 ]. Moreover, objective assessments are considerably fewer than subjective ones, posing greater methodological challenges and difficulties [ 8 ]. Considering the importance of the objective knowledge of medical phenomena in general, masticatory performance included, we have chosen a method of assessment based on sieving the comminuted food, which is one of the most used in this regard [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the selected groups, it was found that the DC group showed superior masticatory e ciency. It was not possible to notice a signi cant difference between the MDI and CRD groups, however, in relation to the Oral Health-Related Quality of Life score, patients with MDI showed more favorable results in relation to those of the CRD 20 .…”
Section: Discussionmentioning
confidence: 71%
“…8,9 The MP index can be assessed using standardised tests which analyse the ability to grind or mix food. 10,11 A suitable method for edentulous subjects is the mixing-ability test based on colorimetric technique measurement. 7 The degree of mixing of a two-colour material (usually a two-colour chewing gum) is evaluated visually on a reference scale or optoelectronically.…”
Section: Introductionmentioning
confidence: 99%